Advanced lung cancer inflammation index and its predictive value for all-cause and cardiovascular mortality among osteoarthritis patients: a NHANES-based study from 2001 to 2018 - Wu, Guiyou; Gu, Dongqiang; Jia, Haigang; Hong, Lei; Wang, Xishun (Frontiers in Medicine, 2025)
BackgroundGlobally, the occurrence of osteoarthritis (OA) is increasing, and the intensity of the condition is frequently determined by the level of inflammation and nutritional status in a person. The Advanced Lung Cancer Inflammation Index (ALI), a pioneering metric, merges two pivotal elements. For instance, it integrates markers of inflammation with measures of nutritional status. This research seeks to delineate the link between ALI and the risk of mortality, whether from universal causes or cardiovascular disease (CVD), particularly in the OA-affected population.MethodsThis research drew upon the National Health and Nutrition Examination Survey (NHANES) database from 2001 to 2018. The study aimed to thoroughly examine the potential association between the ALI and the risk of all – cause as well as CVD – related mortality in patients with OA. The analysis employed weighted Kaplan–Meier methods to estimate survival probabilities and multivariate-adjusted Cox regression models to quantify hazard ratios, adjusting for confounding variables. To assess potential nonlinear associations between ALI and mortality outcomes, a restricted cubic spline (RCS) approach was implemented. Additionally, stratified analyses (e.g., by age, sex, or comorbidities) and interaction tests were conducted to evaluate effect modification and validate the robustness of findings across subgroups. These methodological strategies ensured comprehensive exploration of the ALI-mortality link in OA patients while minimizing bias and enhancing generalizability.ResultsThis research delved into the health records of 2,133 individuals, revealing a notable connection: those with OA and higher ALI scores exhibited significantly lower rates of both overall and CVD-related fatalities. Specifically, a non-linear relationship characterized by an L-shaped curve was observed, indicating that ALI scores below a critical threshold (inflection point at 61.18) were associated with progressively elevated mortality risks, while scores above this threshold exhibited a protective effect against mortality. This pattern was consistent for both all-cause and CVD mortality outcomes, underscoring a threshold-dependent modulation of risk by ALI in OA patients. A subgroup analysis showed a stronger link between ALI scores and all-cause mortality in female OA patients, while no significant interaction was found concerning CVD mortality. Furthermore, time-dependent Receiver Operating Characteristic (time-ROC) curve analysis emphasized the strong predictive ability of the ALI.ConclusionThis cohort study shows that ALI is effective in forecasting mortality outcomes for OA patients, highlighting its clinical significance for risk assessment and prognosis in this population.